EFFECTIVENESS OF THE USAGE OF COOPERATIVE LEARNING MODEL FOR MAKE A MATCH AND TALKING STICK TYPE ON MATHEMATICS LEARNING OUTCOMES OF THE SEVEN GRADE STUDENTS - Faizatun Annisa; Edi Prajitno (Universitas Ahmad Dahlan, 2018)
Exciting and Innovative Learning and Student enthusiasm can influence to the student learning outcomes. This thesis aims to know whether there is a difference between the results of mathematics learning using a cooperative learning model for Make a match and Talking stick type. Then, it also aims to know which learning model is more effective between the cooperative learning model for Make a match type and Talking stick type to the mathematic learning outcomes of the seven-grade student of SMP Muhammadiyah 2 Gamping at Even Semester in 2016/2017 Academic Year. The type of this research is included in experimental research. The populations in this research are all seven grade students of SMP Muhammadiyah 2 Gamping at Sleman Regency in the 2016/2017 academic year, consisting of three classes with the total number of students 108. This research sample is seven-grade student A as the experimental class I, seven-grade student B as the experimental class II and seven-grade student C as the test class. Purposive sampling technique is used as a sample selection. The research instrument is a test of mathematic learning outcomes in the form of multiple-choice questions. Instrument test includes validity test, different ability test, and reliability test. The data analysis technique used in this research is a prerequisite analysis test consisting of normality test and homogeneity test. Hypothesis test uses a t-one side test and a t-two side test. The result of the research shows that the t-two side test with 5% significances and 67 degrees of freedom achieves the value of = 0,2278 and = 1,99601. It means that there is no difference between the value of mathematic learning outcomes of the student using a cooperative learning model for Make a match type and Talking stick type.